Tightly-wound vortex and self-generated intake distortion effects on turbomachinery performance - di Cugno, Domenico (Cranfield University, 2013)
Current developments of civil and military applications may require the installation of aero-engines embedded into the aircraft structure. Consequently, complex diffusing Sducts are necessary to convey air from the intake to the compressor. In addition, civil applications require the reduction of specific fuel consumption and noise levels. These targets can be met by increasing the engine mass flow and reducing the specific thrust by increasing the bypass ratio. In underwing installations there is an increased tendency of ground vortex creation. Generally, the application of complex S-shaped intakes as well as the ingestion of vortices can lead to inlet flow distortion in terms of total pressure and swirl. Consequently, blade vibrations and changes in turbomachinery performance are likely to occur. The aim of this research is to provide qualitative and quantitative information regarding the effect on a fan rotor performance caused by the self-generated distortion of an S-duct and its combination with that attributed to a tightly-wound vortex. A purely numerical coupled system S-shaped intake/fan rotor configuration was defined in this research to analyze the effect of total pressure combined with swirl distortion on the fan rotor performance. Steady-state CFD simulations were carried out on this system by considering clean conditions and, for the first time, the vortex ingestion at the intake inlet and with the rotor operating at two different rotational speeds. Under clean inlet conditions, the self-generated distortion of the S-duct causes a degradation of rotor performance. Moreover, the rotor operability range reduces significantly due to a localized blade overloading. On the other hand, as a vortex is ingested in the system, this interacts with the self-generated distortion in different manners depending on the location and polarity of the vortex itself. Consequently, the level of flow distortion at the AIP changes accordingly. The sign of the change in rotor corrected mass flow is essentially established by the polarity of the vortex ingested. Therefore, the effect of the swirl is predominant compared to that of the total pressure distortion. In particular, the vortices ingested at the centre of the intake inlet plane cause the largest change in rotor corrected mass flow. Regarding the loss of stability pressure ratio, this is established by the swirl distortion even though the effect of total pressure distortion is also notable. Amongst the case studies characterized by low total pressure distortion, a swirl distortion correlation is defined between the loss of stability pressure ratio and the mass flow average of the relative rotor incidence change calculated at the aerodynamic interface plane. A scatter between the CFD results and the established correlation can be attributed to the variations in total pressure distortion. In addition, a CFD based methodology was assessed to determine the location of the aerodynamic interface plane for swirl distortion. This was applied on the datum NASA Rotor 67 configuration working with a vortex ingested at different span locations and for two relevant operating conditions. The outcome of this analysis confirms that, in the worst scenario, the location of the aerodynamic interface plane is located in a position that is an order of magnitude closer to the rotor face compared to what established by previous research for total pressure distortion. This finding would allow the application during the experiments of shorter upstream ducts than that required for total pressure distortion. However, the assessment of a methodology providing a more precise information on location of the aerodynamic interface plane for total pressure distortion would be necessary.